Cendawan Endofit Nonpatogen Asal Tanaman Cabai dan Potensinya sebagai Agens Pemacu Pertumbuhan - Evan P. Ramdan; Widodo Widodo; Efi Toding Tondok; Suryo Wiyono; Sri Hendrastuti Hidayat (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Endophytic fungi have been reported to have mutual symbiosis with their host. This research aimed to obtain nonpathogenic isolates of endophytic fungi from roots, stems, and branches of chili pepper. Endophytic fungi were isolated on 10% malt extract agar (MEA) after serial surface sterilization of plant parts. The effect of endophytic fungi on the development of chili pepper seeds were tested by growing seeds on media containing endophytic fungi isolate. As many as 138 isolates of endophytic fungi were successfully isolated from chili pepper plants from Garut and Bogor. Based on colony morphology the isolates can be differentiated into 9 morphotypes. Among the total isolates, 13.04% are nonpathogenic. Some of them (7,25%) do not effect seedling significantly compared to control and some isolates (5.79%) caused better seedling growth than control. Endophytic fungi having the potential to promote plant growth was identified as Aspergillus sp., Fusarium sp., Penicillium sp., sterile hyphae 1, 2, and 3.